"They are mar-vel-ous, and they all want me!": Gay Brazilian tourists and global geographies of desire. (December 2020) - Jarrin, Alvaro; Pitts, Bryan
This article explores the geographies of desire that inform contact between gay Brazilian tourists and the men they encounter abroad. It argues that Brazilian men largely embrace the sexualized image of themselves that circulates globally and value foreign men according to their proximity to whiteness. By studying tourists who hail from the Global South, their imaginings of the Global North, and the ways they exoticize themselves, the article brings a new perspective to the scholarship on tourism, which usually focuses on North-to-South travel.